A performance appraisal of the global survey and the fully automated methods of Forbush event identification and timing using small-amplitude Forbush decreases - Okike, O; Menteso, F M (RAS techniques and instruments, 2024)
Forbush decrease (FD), commonly defined as an abrupt reduction in the time-intensity flux of cosmic rays (CRs), is one of the long-investigated astrophysical phenomena. Though the subject has received considerable attention, the peculiarities of each event and different varieties of FDs still present them as the most spectacular and intractable CR intensity variations. Their unpredictable forms and diversities make accurate identification and precise timing of the events difficult. Event selection has remained predominantly manual up to the present era of high-speed and sophisticated computer software. Several catalogues appear in the literature. But no two event lists are comparable. The significant disparities among FD catalogues have led to many conflicting and controversial submissions. A comprehensive validation study of FD lists and their methods of selection are some of the important steps to settle or minimize the age-long disputes in the strongly disputed CR influence on space weather. Such a study will guarantee result reproducibility. Two comprehensive FD catalogues, prepared by the global survey method (GSM) and the recently developed fully automated method (FAM), are well suited for such a test. Our results show that the FAM is more efficient and accurate than the GSM. The presence of many other CR phenomena that constitute noise when timing/calculating the magnitude of small FDs requires both numerical filtering and harmonic analysis to handle. FAM is equipped with various subroutines that perform such analytical transformations and other rigorous analyses.